Investigative journalism as a facilitator of parliamentary control of the CESID-CNI: The press and the interventions of espionage directors in Congress - Rueda Rieu, Fernando (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
This article analyzes the information published by the media about the CESID and the CNI, to discover to what extent it has given rise to control actions in the Congress of Deputies. It also studies the occasions in which the directors of the intelligence service went to Parliament to inform and if the topics they spoke about came from information uncovered by the press. As can be seen, parliamentary control increased after the creation of the CNI in 2002 and an important part can be attributed to the role of investigative journalism.